Mechanical tuning methodology on the barrier configuration near a piezoelectric PN interface and the regulation mechanism on I–V characteristics of the junction. (March 2021) - Yang, Wanli; Liu, Jinxi; Hu, Yuantai
Abstract: In this paper, study on the whole-domain coupling between electromechanical fields and charge carriers inside a piezoelectric PN junction is conducted in detail by abandoning the traditional depletion layer approximation and the low injection assumption. The barrier region of a PN junction has been fully opened in order that the upheaval change of electric field and carrier concentrations near the interface can be clearly exhibited and the evolution laws of potential barrier configuration with mechanical loadings can be thoroughly observed by taking into account the three basic motion modes of charge carriers (drift, diffusion and recombination). Effect of mechanical loadings on performance of piezoelectric PN junctions is further delineated from those changes induced by loadings, including the increment of electric field, the carrier redistribution modes and the disturbance laws of energy levels. It is found that the interface barrier configuration can only be significantly tuned by such a mechanical loading mode that the majority carriers are driven into the barrier region from the two sides to induce local carrier-inversion, while the carrier-inversion phenomenon is shown to be helpful for tuning the recombination rate of electrons and holes. As for the loaded configuration, the locations should be chosen according to that the mechanical loadings can cause the structure within an appropriate length near the PN interface into deformation to produce suitable tuning effect to the nearby barrier. Obviously, an effective mechanical tuning methodology on the potential barrier nature near a piezoelectric PN interface has been formed naturally. On this foundation, both the barrier configuration and the inner recombination rate of carriers can be expediently designed and controlled to realize the optimal conversion between electron current and hole current. Further analysis on a non-equilibrium piezoelectric PN junction subjected to a forward bias voltage shows the regulated mechanism of mechanical loadings on I–V characteristics of a piezoelectric PN junction as follows: the holes/electrons, passing through the PN interface from the p/n-zone into the n/p-zone in the form of majority-carrier current, enter into the recombination mode with the local electrons/holes, which induces the electrons/holes in the right/left sides to flow toward the central barrier region. Such a process indicates that the mutual conversion mechanism between two majority-carrier currents across the interface is just implemented by recombination of charge carriers near the barrier region. Thus, the regulation laws of mechanical loadings on the I–V characteristics of a piezoelectric PN junction are finally illustrated from tuning the potential barrier configuration near the interface and optimizing the recombination rate of electrons and holes in the barrier region. Obviously, study on this topic possesses referential significance to mechanical tuning the performance of piezoelectric PN junctions and piezotronic devices. Graphical Abstract: ga1 Highlights: Barrier region of a piezoelectric PN junction was opened with considering all the three basic motion modes of carriers. The barrier configuration can be tuned by loadings with majority carriers driven into the central region from two sides. Regulation mechanism on I-V characteristics was revealed from tuning barrier configuration and recombination rate.